Якісна вища менеджерська освіта – умова ефективності економічних реформ в Україні - Лінькова, Олена Юріївна (Національний технічний університет "Харківський політехнічний інститут", 2023)
Якісна вища освіта формує національну конкурентоспроможність та зміцнює статус країни у глобальній економіці. В роботі доведено актуальність забезпечення якості вищої освіти в галузі менеджменту через зони впливу на: людину, її життєву позицію, оточуючий світ і майбутнє. Систематизовано: актуальні виклики до практичної діяльності менеджерів в Україні: реінжиніринг бізнес-процесів з використанням штучного інтелекту; формування проєктних команд на основі холократії; вимоги щодо прискорення прийняття управлінських рішень; розвиток персоналу за програмами інновацій та професійного інтелекту; розвиток емоційного інтелекту менеджера та аутентичного лідерства з метою підвищення продуктивності проєктної діяльності; коучінг менеджмент для концентрації індивідуальних можливостей найманих працівників при виконання бізнес-завдань; підвищення стресо стійкості менеджера; та виклики щодо якісної підготовки менеджерів у вітчизняних вищих навчальних закладах: учасники освітнього процесу, які опинилися в епіцентрі бойових дій, зазнали значних психічних і фізичних травм; вимушено переміщені із зони активних бойових дій, зазвичай стикаються з проблемами соціальної адаптації; пошкоджена та зруйнована інфраструктури; повернення вимушено переміщених учасників освітнього процесу; реалізація політики реформування сфери освіти на всіх рівнях: удосконалення галузевих стандартів вищої освіти, з урахуванням новітніх технологій; діджиталізація освіти; невідповідність матеріально-технічної бази освітніх установ технологічному розвитку дослідницьких, операційних процесів; методичне забезпечення відповідно до оновлених вимог галузевих стандартів вищої освіти; рівні можливості (прозорість та повнота інформації) для отримання якісної освіти. В роботі автором структуровано заходи щодо їх подолання сучасних викликів в сфері вищої менеджерської освіти за напрямами: інноваційного менеджменту вищого навчального закладу; актуалізації стратегій закладу освіти з підготовки менеджерів за кожною глобальною проблемою (забруднення екосистем – стратегія інтеграційного зростання за рахунок впровадження сумісних проєктів із екологічного менеджменту різних освітніх програм і кооперації освітніх закладів різних країн; низькі темпи росту економіки – стратегія диверсифікації через формування освітніх проєктів з менеджменту, щодо реструктуризації господарюючих суб’єктів на основі можливостей штучного інтелекту; енергетична та продовольча кризи – стратегія інтенсивного зростання через формування нових логістичних систем в Україні; діджиталізація та технологічний розвиток – стратегія скорочення адміністративних витрат вищого навчального закладу через запровадження проєктів практичної підготовки студентів за програмою менеджменту); інвестування програм навчання викладачів. Наведені заходи, що сприяють розвитку вищої освіти в галузі менеджменту: діалог навколо викладання та навчання на міжнародному рівні; інноваційні творчі викладацькі практики із високим рівнем впливу; інноваційні освітні технології; сумісні дослідження викладачів і студентів у галузі менеджменту; інтеграція науково-інноваційної системи України до європейського дослідницького простору; інтелектуальні обговорення та дебати у міждисциплінарному контексті при підготовці менеджерів. Зазначено питання для проведення подальших досліджень: інтеграція індивідуальних траєкторій навчання студентів у структуру навчальних планів вищих навчальних закладів за різними освітніми програмами.

Quality higher education forms national competitiveness and strengthens the country's status in the global economy. The work proves the relevance of ensuring the quality of higher education in the field of management through zones of influence on: a person, his position in life, the surrounding world and the future. Systematized: actual challenges to the practical activity of managers in Ukraine: reengineering of business processes using artificial intelligence; formation of project teams based on holocracy; requirements for speeding up management decision-making; personnel development according to programs of innovation and professional intelligence; development of a manager's emotional intelligence and authentic leadership in order to increase the productivity of project activities; coaching management to concentrate the individual capabilities of employees in the performance of business tasks; increasing the manager's stress resistance; and challenges regarding high-quality training of managers in domestic higher educational institutions: participants in the educational process, who found themselves in the epicenter of hostilities, suffered significant mental and physical injuries; forcibly displaced from the zone of active hostilities, usually face problems of social adaptation; damaged and destroyed infrastructure; return of forcibly displaced participants of the educational process; implementation of the policy of reforming the sphere of education at all levels: improvement of industry standards of higher education, taking into account the latest technologies; digitization of education; inconsistency of the material and technical base of educational institutions with the technological development of research and operational processes; methodological support in accordance with the updated requirements of industry standards of higher education; equal opportunities (transparency and completeness of information) to obtain quality education. In the work, the author structured measures to overcome modern challenges in the field of higher management education in the following directions: innovative management of a higher educational institution; updating the educational institution's strategies for training managers for each global problem (pollution of ecosystems - a strategy of integrated growth due to the implementation of compatible projects on environmental management of various educational programs and cooperation of educational institutions of different countries; low rates of economic growth - a strategy of diversification through the formation of educational projects on management, regarding the restructuring of business entities based on the capabilities of artificial intelligence; energy and food crises - a strategy of intensive growth through the formation of new logistics systems in Ukraine; digitalization and technological development - a strategy for reducing administrative costs of a higher educational institution through the introduction of projects for practical training of students under the management program) ; investing in teacher training programs. The following measures contribute to the development of higher education in the field of management: dialogue around teaching and learning at the international level; innovative creative teaching practices with a high level of impact; innovative educational technologies; joint research of teachers and students in the field of management; integration of the scientific and innovative system of Ukraine into the European research space; intellectual discussions and debates in an interdisciplinary context in training managers. The issue for further research is indicated: the integration of individual student learning trajectories into the structure of curricula of higher educational institutions according to various educational programs.
Quality higher management education is a condition for the efficiency of economic reforms in Ukraine
Keywords: якість; ефективність; реформа; освіта за програмою менеджмент; конкурентні переваги; культура; бізнес-модель; екологічний менеджмент; реінжинірінг; quality; efficiency; reform; management education; competitive advantages; culture; business model; environmental management; reengineering